2018
DOI: 10.4314/tjpr.v17i3.10
|View full text |Cite
|
Sign up to set email alerts
|

Tris-diamine-derived transition metal complexes of flurbiprofen as cholinesterase inhibitors

Abstract: Purpose:To synthesize novel tris-diamine-derived transition metal complexes of flurbiprofen M(C2H8N2)3 (fp)2 and M(C3H10N2)3 (fp)2, and to evaluate their acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) inhibitory activities. Method: Tris-diamine-derived transition metal complexes of Co(II), Ni(II), and Mn(II) were synthesized and characterized using ultraviolet-visible (UV-Vis) spectroscopy, Fourier transform-infrared (FT-IR) spectroscopy, elemental analysis, magnetic susceptibility, conductivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…12. Few Schiff bases used for complexation with metals by You et al [124,125] The Schiff base manganese complexes exhibit catalytic activity [126][127][128][129] and form polymeric structure through thiocyanato ligand. Recent studies indicated that Cu(II), Cd(II), Co(II,III) and Ni(II) complexes with Schiff base ligands display urease inhibitor activity.…”
Section: + +mentioning
confidence: 99%
“…12. Few Schiff bases used for complexation with metals by You et al [124,125] The Schiff base manganese complexes exhibit catalytic activity [126][127][128][129] and form polymeric structure through thiocyanato ligand. Recent studies indicated that Cu(II), Cd(II), Co(II,III) and Ni(II) complexes with Schiff base ligands display urease inhibitor activity.…”
Section: + +mentioning
confidence: 99%
“…These results showed that the metal ions and ligands played an important role in urease inhibition. Besides, complex 40 with Mn (III) ions was synthesised 73 . However, the results of urease inhibition displayed that compound 40 (IC 50 = 61.05 μM) showed moderate urease inhibition on this enzyme as compared with thiourea, which was tested as the reference standard with an IC 50 value of 21.25 μM ( Figure 11 ).…”
Section: Metal-based Urease Inhibitorsmentioning
confidence: 99%